Mapping Labour Migration’s Influence on Immigration, Refugee Policies, and Beyond - Hoo, Wong Chee; Annamalah , Sanmugam; Ahmed, Selim; Sentosa , Ilham (Journal of Ecohumanism, 2025)
The intricate tapestry of human migration and development unfolds a rich exploration into the multifaceted dynamics of movement, traversing a spectrum from voluntary to involuntary transitions that intricately shape the global landscape. Beyond the conventional trajectories of travel, education, job shifts, and relocation prompted by employment or marriage, lies the complex realm of labour migration. Within this realm, individuals embark on journeys to foreign shores in pursuit of employment opportunities, often driven by the dearth of viable prospects in their countries of origin. Within this narrative, stark contrasts emerge, as some individuals find themselves ensnared in the web of human trafficking orchestrated by unscrupulous brokers, while others discover avenues for personal growth, self-realization, and societal ascension in their host countries. The exploration gains depth and nuance when focused on the experiences of a singular immigrant woman, prompting a cascade of inquiries into strategies for overcoming the financial hurdles of migration, the educational background that shaped in home country, and the dynamics of the consumer base for the products she contributes to in the host country. Moreover, the reverberations of the remittances back to the place of origin touch the lives of the family and community, raising questions about the potential for family reunification in the host country. This study of human migration and development transcends the confines of academic discourse to intricately entwine with the fabric of our daily lives. It serves not only to broaden our horizons to encompass the conflicts, disasters, and poverty that propel migration but also to prompt profound reflection on the immigration and refugee acceptance policies of diverse nations. As we navigate this complex web of human mobility, we glean insights into the underlying forces that shape the trajectories of migration and development, and the consequential impacts on both individuals and societies. Through this comprehensive examination, we are compelled to reckon with the intricate intersections of human experience, policy frameworks, and global dynamics, striving for a more inclusive and equitable approach to migration governance.